2010
DOI: 10.1111/j.1753-6405.2010.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of health status and health services utilisation between Indigenous and non‐Indigenous infants in Australia

Abstract: Objective: To examine the differences in health services utilisation and the associated risk factors between Indigenous and non‐Indigenous infants at a national level in Australia. Methods: We analysed data from a national representative longitudinal study, the Longitudinal Study for Australian Children (LSAC) starting in 2004. We used survey logistic regression and survey multiple linear regression to examine the factors associated with health services utilisation. Results: Health status of Indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…However, our previous studies using the similar data had found that Indigenous children were more likely to have poor physical health outcomes, were twice likely to have a medical condition or disability, and were more likely to have medical care needs compared to their non-Indigenous counterparts [9, 32]. The current study also demonstrated that there were higher proportions of Indigenous children whose health status were fair or poor, suggesting more needs in health care.…”
Section: Discussionsupporting
confidence: 67%
“…However, our previous studies using the similar data had found that Indigenous children were more likely to have poor physical health outcomes, were twice likely to have a medical condition or disability, and were more likely to have medical care needs compared to their non-Indigenous counterparts [9, 32]. The current study also demonstrated that there were higher proportions of Indigenous children whose health status were fair or poor, suggesting more needs in health care.…”
Section: Discussionsupporting
confidence: 67%
“…28 Therefore, socio-economic measures which are known to influence BMI were included to adjust for this potential source of confounding. The socioeconomic measures chosen were (i) combined weekly income of caregivers (in thousands); (ii) whether the child was of Australian Aboriginal or Torres Strait Islander heritage (binary variable); 29 (iii) whether the child spoke a language other than English at home; and (iv) the number of years of education the mother had received. Maternal education years were calculated according to the methodology of Blakemore, Gibbings and Strazdins, 30 where the total number of years that the mother had received education are placed on a scale ranging from 0 (that is, never attended school) to 20 (completed postgraduate degree).…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander (hereafter, Aboriginal Australian) children experience inferior health outcomes when compared to other Australian children and this includes higher rates of disability [1,2]. The issues around Aboriginal childhood disability are complex and multifaceted.…”
Section: Introductionmentioning
confidence: 99%